Oxygen broadening and shift coefficients in the ν6 band of methyl iodide (12CH3I) at room temperature. (December 2019) - Attafi, Y.; Galalou, S.; Kwabia Tchana, F.; Vander Auwera, J.; Ben Hassen, A.; Aroui, H.; Perrin, A.; Manceron, L.; Doizi, D.
Highlights: Fourier transform spectra of the ν6 band of methyl iodide (CH3 I). Measured of oxygen broadening and shift coefficients in the ν6 band of CH3 I. Modeling of the J and K dependences of the O2 -broadening coefficients. Generation of CH3 I-air broadening coefficients. Abstract: In this study we report the high-resolution measurements of oxygen pressure- broadening and pressure-induced shift coefficients for rovibrational transitions in the ν6 band of methyl iodide ( 12 CH3 I), centered at 892.918 cm –1 . The results were obtained by analyzing fourteen high-resolution room temperature laboratory absorption spectra with a mono-spectrum non-linear least squares fitting of Voigt profiles. The data were recorded with the Bruker IF125HR Fourier transform spectrometer located at the LISA facility in Créteil, using a White type cell with a path length of 564.9 cm and total pressures up to 295 hPa. The measured oxygen-broadening coefficients range from 0.0648 to 0.1207 cm –1 atm –1 at 295 K. The measured shift coefficients were all negative and varied between −0.00044 and −0.04984 cm –1 atm –1 . The average accuracy on the measured O2 -broadening coefficients and pressure shift coefficients was estimated to about 4% and 11%, respectively. The O2 -broadening coefficients obtained in the present work are compared with values reported in the literature for the ν5 band of CH3 I, showing a satisfactory agreement with an average difference of about 8%. The shift coefficients are compared with values reported in the literature for the ν6 band of CH3 F-Ar system, exhibiting the same order of magnitude and trend. The J and K rotational dependences of the O2 -broadening coefficients have been observed and the latter modeled using empirical polynomial expansions. On average, the empirical expression reproduces the measured O2 -broadening coefficients to within 3%. Using the measured broadening coefficients of the CH3 I-O2 and CH3 I-N2 [Attafi et al., J Quant Spectrosc Radiat Transf 231 (2019) 1–8] systems, we produced CH3 I-air broadening coefficients, ranging from 0.0783 to 0.1385 cm –1 atm –1 at 295 K. The present results and the data already available should be valuable not only for predicting the CH3 I infrared spectrum in the atmosphere, but also for verifying theoretical calculations of pressure-broadening and pressure-shift coefficients in the ν6 region of methyl iodide spectra. Graphical abstract: Image, graphical abstract